2012
DOI: 10.1002/app.38503
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of superhydrophobic fabric coating using microphase‐separated dodecafluoroheptyl‐containing polyacrylate and nanosilica

Abstract: Superhydrophobic coating was developed on cotton fabric in this article using a dodecafluoroheptyl-containing polyacrylate (DFPA) and nanosilica. Film morphology of DFPA on cotton fibers/fabrics and chemical compositions of the treated cotton fabric were investigated using scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS), respectively. DFPA could form a relatively even film on the cotton fabric/fiber under SEM observation; however, it presented a rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…It is well known that superhydrophobic/superoleophobic surfaces are usually inspired by many biological materials in nature exhibiting an unusual superhydrophobicity/superoleophobicity and self‐cleaning property, such as lotus leaves, rice leaves, red rose petals, butterfly wings, cicada wings, gecko feet, desert beetle, spider silks, and fish scales . Based on the previous reported literatures, it has been found that the presence of special micro/nanostructures and low‐surface‐energy materials on these surfaces are critical for the formation of the superhydrophobicity/superoleophobicity . To mimic the effect, enormous contributions have been made to the design and fabrication of superhydrophobic surfaces via two kinds of approaches: either creating rough structures on low‐surface energy substrates or chemically modifying rough substrates with low‐surface energy materials …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that superhydrophobic/superoleophobic surfaces are usually inspired by many biological materials in nature exhibiting an unusual superhydrophobicity/superoleophobicity and self‐cleaning property, such as lotus leaves, rice leaves, red rose petals, butterfly wings, cicada wings, gecko feet, desert beetle, spider silks, and fish scales . Based on the previous reported literatures, it has been found that the presence of special micro/nanostructures and low‐surface‐energy materials on these surfaces are critical for the formation of the superhydrophobicity/superoleophobicity . To mimic the effect, enormous contributions have been made to the design and fabrication of superhydrophobic surfaces via two kinds of approaches: either creating rough structures on low‐surface energy substrates or chemically modifying rough substrates with low‐surface energy materials …”
Section: Introductionmentioning
confidence: 99%
“…Effect of textile treatment on its pristine color is expressed as whiteness of the fabrics before and after being treated, which can be determined by a whiteness tester. In addition, bending rigidity (BR) is one of the determining factors in assessing the fabric handle . A decrease in the BR leads to a desirable fabric handle.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that properties and application performance of a polymer depend largely on its structure or morphology on substrates . Film morphology does not only affect the surface and performance properties of a polysiloxane but also provide information about the orientation of a film‐forming molecule in an absorbed state, and reveal the film‐forming mechanism .…”
Section: Resultsmentioning
confidence: 99%
“…The activated cotton textiles, ACT was made of dipping, drying and annealing processes which were carried out by dipping the textile in 1 M NaF solution for 1 h and drying at 120°C, followed by annealed in tubular furnace at 800-1200°C in argon atmosphere for an hour. Counter electrode, Pt foil and working electrode, ACT was immersed into the electrolyte solution of equimolar 0.1 M solution of Mn (CH 3 COO) 2 and Na 2 SO 4 . A constant current 1 mA/cm 2 was applied for 30-240 min to coat the MnO 2 , and then fabrics were washed with deionised water to remove the electrolyte and then dried in oven at 100°C for 3 h. Such fabrics have resistivity of 10-20 Ω/sq which is enough to get the supercapacitor behaviour on the textiles.…”
Section: Nanoparticles Coatingmentioning
confidence: 99%